2022
DOI: 10.1039/d2ce00236a
|View full text |Cite
|
Sign up to set email alerts
|

High-Tp-triggered phase transition exhibiting switchable dielectric–thermal responses and long photoluminescence lifetime in a novel inclusion luminophor

Abstract: Materials combining high-temperature phase transformation and fluorescence properties are not abundant, especially stator-rotator-type inclusion compounds which have excellent optical properties are extremely rare. In this paper, a neoteric high-temperature crown...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The dielectric constant curve of 1 shows that there is a reversible step-like dielectric anomaly near T c . Similarly, for the cooling process, it can be found that the dielectric constant curve follows a trajectory similar to that of the heating cycle . The significant dielectric switching during heating–cooling makes composite materials an energy storage and switching material …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The dielectric constant curve of 1 shows that there is a reversible step-like dielectric anomaly near T c . Similarly, for the cooling process, it can be found that the dielectric constant curve follows a trajectory similar to that of the heating cycle . The significant dielectric switching during heating–cooling makes composite materials an energy storage and switching material …”
Section: Resultsmentioning
confidence: 89%
“…Similarly, for the cooling process, it can be found that the dielectric constant curve follows a trajectory similar to that of the heating cycle. 25 The significant dielectric switching during heating−cooling makes composite materials an energy storage and switching material. 26 Then, we measured the single crystal structure of 1 at 296 K (LTP).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18-crown-6 (1, 4, 7, 10, 13, 16hexaoxacyclo-octadecane), a common host ligand, consists 6 oxygen atoms and can fix a guest amine cation by NÀ H•••O hydrogen-bonding interactions, forming a solid host-guest inclusion system and attracting the interest of scientists to exploit it. [12][13][14][15] Many phase change materials with this hostguest inclusion have been reported. Ye and Zhang's group reported [(4-fluorobenzylammonium)(18-crown-6)][ClO 4 ] and [(4-chlorobenzylammonium)(18-crown-6)][ClO 4 ], which have nonlinear optical and photoluminescence bistable switching response characteristics in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Tan and Tang's group screened a neoteric host-guest containing crystal: [(2, 4, 6trifluoroanilinium)-(18-crown-6)][BF 4 ], which has a high dielectric phase change temperature and exhibits a long photoluminescence lifetime. [13] However, there is still a big room for discovering some new structures. Based on dynamic characteristics of phase change, there are plenty of reasons to believe that flexible organic molecules with single CÀ C bond are reasonable guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In our long-term research, it is worth mentioning that we have assembled two examples of host–guest high-temperature 18-crown-6 ferroelectrics with high spontaneous polarizability utilizing flexible and variable cyclohexylamine 16 and adjusted the position of the fluorine atom on the benzene ring to obtain ferroelectric and luminescent materials with high-temperature phase transitions, respectively. 17,18 Besides, an unprecedented homochiral single-component organic ferroelectric experiencing a ferroelectric to ferroelectric phase transition has been reasonably designed and constructed, 19 and achiral/chiral low-dimensional perovskite ferroelectric crystals have been synthesized by controlling the ratio of anions to cations. 20…”
Section: Introductionmentioning
confidence: 99%